1997
DOI: 10.1002/(sici)1099-0518(199703)35:4<769::aid-pola23>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Wholly aromatic thermotropic liquid crystalline polyesters of 3,3?-bis(phenyl)-4,4?-biphenol with 4,4?-benzophenone dicarboxylic acid

Abstract: A series of wholly aromatic, thermotropic polyesters, derived from 3,3′‐bis(phenyl)‐4,4′‐biphenol (DPBP), nonlinear 4,4′‐benzophenone dicarboxylic acid (4,4′‐BDA), and various linear comonomers, were prepared by the melt polycondensation reaction and characterized for their thermotropic properties by a variety of experimental techniques. The homopolymer of DPBP with 4,4′‐BDA had a fusion temperature (Tf) at 265°C, exhibited a nematic phase, and had a liquid crystalline range of 105°C. All of the copolyesters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…To reduce the melt temperature of TLCP, different strategies were utilized, such as introducing flexible spacers,35, 36 using isomerous monomers as mesogenic groups,37–39 introducing nonlinear or kinked monomers,40, 41 random copolymerization of monomers as well as introducing bulky substitute onto mesogenic groups,42–46 hyperbranched topologies, and dendritic architectures 47–49. Zhao et al synthesized P‐TLCP‐FS (Scheme ) by introducing flexible spacers onto the mesogenic chains of P‐TLCP which decreased the melt temperature of P‐TLCP from 290 (P‐20) to 205 °C (P‐TLCP‐FS‐60) 50.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the melt temperature of TLCP, different strategies were utilized, such as introducing flexible spacers,35, 36 using isomerous monomers as mesogenic groups,37–39 introducing nonlinear or kinked monomers,40, 41 random copolymerization of monomers as well as introducing bulky substitute onto mesogenic groups,42–46 hyperbranched topologies, and dendritic architectures 47–49. Zhao et al synthesized P‐TLCP‐FS (Scheme ) by introducing flexible spacers onto the mesogenic chains of P‐TLCP which decreased the melt temperature of P‐TLCP from 290 (P‐20) to 205 °C (P‐TLCP‐FS‐60) 50.…”
Section: Introductionmentioning
confidence: 99%
“…The representative FTIR spectrum of polyester IVHC is shown in Figure 4: 3425 (overtone of C=O), 21 2975, 2938 (aliphatic), 1744 (ester carbonyl), 1696 (C=O of cyclopentanone ring), 1604 (C=C aromatic) 1287 to 1016 cm -1 (C–O–C of ester).…”
Section: Resultsmentioning
confidence: 99%
“…During this study, it was found that the q of PPT is 753.5 Å which demonstrates its rigidity and LC behaviour. A previous simulation for PPT reports [62][63][64] the value of qZ751 Å which is in a good agreement with the result obtained using the parameters proposed for this study.…”
Section: Resultsmentioning
confidence: 99%
“…A critical value of q r of 5 suggests a nematic isotropic transition temperature [62][63][64] (T i ). During this study it was observed that at high temperature the molecules adopt, on average, a coiled conformation with a low persistence length but on reducing the temperature the width of the distribution about the straight conformation narrows and the persistence length increases.…”
Section: Resultsmentioning
confidence: 99%